Kunstwerken verworven door de Vlaamse Gemeenschap in 1988-1989. (Brussel : Dienst Beeldende Kunst en Musea, 1990)
Ausloos, Paul ; Van Beeck, Martien ; Ben-Kiki, Vered ; Bervoets, Fred ; Bijl, Guillaume ; Bijtebier, Jean-Marie ; Bilquin, Jean ; Bleus, Guy ; Van Bossche, Guy ; Van Braeckel, Malou ; Braeckman, Dirk ; Bruneau ; Brusselmans, Luc ; Bruyninckx, Rob ; Brys, Edwin ; Buisman, Sjoerd ; Van Caeckenbergh, Patrick ; Callens, Mario ; Carlier, Jan ; Charlton, Alan ; Chlanda, Marek ; Claus, Luc ; de Clercq, Hugo ; Coeckelberghs, Luc ; Copers, Leo ; de Cordier, Thierry ; Corillon, Patrick ; Cuykx-Boulez, Betty ; Daems, Walter ; DC, Franky ; Deacon, Richard ; Debaere, Hugo ; Deconynck, Jan ; Deknock, Anne ; Deleu, Luc ; Delvoye, Wim ; Derick, Lief ; Dessauvage, Tjok ; Dimitrijevic, Braco ; Droste, Monica ; Duchateau, Hugo ; Duval, Marion ; Eecken, Dirk Vander ; Engeln, Franklin ; Fabre, Jan ; Fierens, Kris ; de Fraeye, Mark ; García Sevilla, Ferran ; Gees, Paul ; Geirlandt, Toni ; Gentils, Vic ; Van Gestel, Fik ; Geysels, Ludo ; Goethals, Marc ; Grossen, Luc ; Gruyaert, Harry ; Hamelrijck, Ado ; Hautman, Sigefride Bruna ; Hien, Albert ; Hoorne, Emiel ; Van Houtte, Kathleen ; Inan, Ergin ; Van Isacker, Philip ; De Jaeger, Stefan ; Kellens, Stefan ; Kemps, Niek ; De Keyser, Raoul ; Lafontaine, Marie-Jo ; Laib, Wolfgang ; Lakke, Allart ; Lebeau, Philippe ; Leccia, Ange ; Lohaus, Bernd ; Luyten, Mark ; Maes, Agnes ; Maet, Marc ; Matthys, Danny ; Mees, Guy ; Michielsen, Bart ; Mulkers, Urbain ; Nordman, Maria ; van Oost, Jan ; De Pelsmaeker, Lieve ; Pistoletto, Michelangelo ; Puckey, Tom ; Queeckers, Bernard ; Van Rafelghem, Paul ; Raveel, Roger ; Roelants, Karel ; Rombouts, Guy ; Rubens, Albert ; Sack, Stephen ; Sanches, Rui ; De Sauter, Willy ; Schietekat, Jan ; Selleslags, Herman ; De Smet, Eric ; Van Sompel, Willy ; Van Soom, Luk ; Stroobant, Dominique ; Suls, Jeron ; etc.
boek